STUDI POPULASI DAN TINGKAH LAKU MONYET EKOR PANJANG (Macaca fascicularis) DI TELAGA BURET KABUPATEN TULUNGAGUNG - Kartikasari, Desi; Ihwanul Muslimin, Muhammad Abdul Irhas; Agustina, Citra Sari; Karsi Nerro Soethamprin (JEAS (Journal of Educational and Applied Science), 2024)
Macaca fascicularis, or long-tailed monkey, is a primate found in Southeast Asia, including Indonesia. Despite its abundant population, the long-tailed macaque is classified as an over-exploited wildlife. Therefore, conservation efforts are needed to prevent the extinction of the long-tailed monkey population. One of the natural habitats of the long-tailed monkey is located in Telaga Buret, Tulungagung Regency. In this area, the total number of long-tailed monkeys is unknown and has never been studied. Therefore, this study aims to determine the population and behavior of long-tailed monkeys in Telaga Buret using the scan sampling method in certain time intervals. The results showed that the total population of long-tailed monkeys found in the study site was 98 individuals. The observed behavioral parameters include moving activities, vocalizing, foraging, playing, searching, sexual, interaction with humans, aggression, resting and parenting. From the results of the study, the behavior that has the highest index value is moving (38%) while the least behavior is interacting with humans (1%). The high values generated from the percentages indicate how often M. fascicularis performed these behaviors at each time interval.